1992
DOI: 10.2135/cropsci1992.0011183x003200010044x
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Silica, and Aluminum Stresses and Varietal Resistance in Rice: Effects on Whitebacked Planthopper

Abstract: Certain physicochemical stresses affect the susceptibility of plants to insects. The objective of this study was to determine the effects of different levels of Fe, Si, and Al on the establishment of Sogatella furcifera (Horvath) on resistant IR2035-117-3 (IR2035) and susceptible Taichung Native 1 (TN1) rice (Oryza saliva L.) cultivars under glasshouse conditions in natural daylight of 12 h, 29/21 °C (day/night), and minimum 70% relative humidity. Insect population increased on rice plants grown in culture sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 0 publications
5
34
0
4
Order By: Relevance
“…These researchers concluded that the non-preference of aphids for silicon-treated leaves was due to a mechanical barrier provided by the deposition of this element on the cell wall. Analogous conclusions have also been drawn from other crops and for other insects (Djamin & Pathak 1967, Tayabi & Azizi 1984, Salim & Saxena 1992, Sawant et al 1994, Goussain et al 2002. Wheat leaves that received silicon sprays were more turgid than those silicon-free ones (control).…”
supporting
confidence: 63%
“…These researchers concluded that the non-preference of aphids for silicon-treated leaves was due to a mechanical barrier provided by the deposition of this element on the cell wall. Analogous conclusions have also been drawn from other crops and for other insects (Djamin & Pathak 1967, Tayabi & Azizi 1984, Salim & Saxena 1992, Sawant et al 1994, Goussain et al 2002. Wheat leaves that received silicon sprays were more turgid than those silicon-free ones (control).…”
supporting
confidence: 63%
“…This higher accumulation of silicon is the reason for low borer damage in plots receiving higher doses of DAE. It has been hypothesized that "Si" deposited on the tissue surface acts as a physical barrier and it prevents physical penetration and / or makes the plant cells less susceptible to enzymatic degradation by insect pests (Salim and Saxena 1992) and (Kvedaras and Keeping, 2007). This mechanism is supported by the positive correlation between the Si content and the degree of suppression of insect pests which is well established through this investigation (Table 3).…”
Section: Silicon Content In Plant Samplesupporting
confidence: 71%
“…Indeed, SiO 2 was in synergy with Ca in rice ironstressed conditions [56]. In contrast SiO 2 is antagonist to N, P, K, and Mg. Van der Vorm [57] observed that high SiO 2 content in nutrients solutions exerted suppressive effects on the contents of Ca and Mg in the leaves of rice and sugarcane.…”
Section: Silica Correlations With Other Leaf Traitsmentioning
confidence: 91%
“…We found high K values in leaves harvested in April and August. This may imply that SiO 2 is either excluded for preferential uptake of K. Indeed, SiO 2 and K antagonistic and synergistic relationships have been documented [56]. Moreover, more silicified leaves i.e.…”
Section: Silica Correlations With Other Leaf Traitsmentioning
confidence: 98%